Уточнение расчетной модели кольцевого лазерного гироскопа на основе экспериментальных данных - Погорелов, Сергей Юрьевич; Счастливец, Кирилл Юрьевич (НТУ "ХПИ", 2005)
In the proposed paper the analyze model accuracy of ring laser gyro has been researched. The temperature fields of real laser gyro have been determinate during the experiment. The analyze model of laser gyro corresponding experiment conditions was create. Difference between experimental and modeling results was analyzed. As result, the analyze model parameters of laser gyro has been adjust and adequacy between experimental and modeling heat processes became more full
Keywords: резонатор; катод; мощность резисторов; тепловые процессы